Loving: A developmental challenge of middle age - Marburg, Galen Sanford (Journal of religion and health, 1986)
The capacity to love fully is one of the central developmental challenges of middle age. Loving is predicated upon the dynamic synthesis of trusting, autonomous, and creative relationships during childhood and adolescence. With the emergence of a productive orientation during middle age, it becomes increasingly clear that it is important to work for that which we love. It is impossible to encapsulate the essence of loving, but it can be partially delineated in terms of care, responsibility, respect, and knowledge. As a loving relationship develops, sexuality may emerge as another phase of mutuality. However, many loving relationships have no sexual overtones. In summary, loving is an end experience, for it engenders the joy that comes from being fully alive.